Formula Penghitungan Tenaga Keperawatan Modifikasi FTE dengan Model Asuhan Keperawatan Profesional Tim - Erlin Kurnia; Nyoman Anita Damayanti; Nursalam Nursalam (Jurnal Ners, 2011)
Introduction: A variety of formulas that can be done to count the needs of nursing staff in inpatient rooms include Ministry of Health Republic of Indonesia method, Gillies, Nina Formulation, Douglas, and Full Time Equivalent (FTE). The purpose of this study was to recommend the formula for calculating nurse staff needs in implementation of team nursing model of care delivery.Method: The design used in this study was a time and motion study. Data was collected by observations and questionnaires. The population was the nurses who work at Kediri Baptist Hospital inpatient wards. The observation and questionnaires to the resource persons utilized as a data collection method. Two inpatient wards were the taken as simulation places, there were Ward A and Ward B. Ward A was taken as simulation place based on FTE method and Ward B was taken as simulation place based on Ministry of Health Republic of Indonesia method. Based on the calculation according to the Ministry of Health Republic of Indonesia method obtained the required number of nursing staff as many as 17 people in Ward A and 23 in Ward B. Meanwhile, according to FTE count obtained the number of nursing staff as many as 20 people in Ward A and 33 in Ward B.Result: The simulation results obtained an increase in performance of duties and job satisfaction of nurses in inpatient wards that were simulated using the FTE method.Conclusio: The inpatient ward that is simulated using the Ministry of Health Republic of Indonesia method obtained an increase in performance of duties but a decrease in job satisfactions. It can be concluded that the FTE method is more appropriate to use than Ministry of Health Republic of Indonesia.